Multiple binding modes of a small molecule to human Keap1 revealed by X‐ray crystallography and molecular dynamics simulation. Issue 1 (30th June 2015) - Satoh, Mikiya; Saburi, Hajime; Tanaka, Tomoyuki; Matsuura, Yoshinori; Naitow, Hisashi; Shimozono, Rieko; Yamamoto, Naoyoshi; Inoue, Hideki; Nakamura, Noriko; Yoshizawa, Yoshitaka; Aoki, Takumi; Tanimura, Ryuji; et al.
Abstract : Keap1 protein acts as a cellular sensor for oxidative stresses and regulates the transcription level of antioxidant genes through the ubiquitination of a corresponding transcription factor, Nrf2. A small molecule capable of binding to the Nrf2 interaction site of Keap1 could be a useful medicine. Here, we report two crystal structures, referred to as the soaking and the cocrystallization forms, of the Kelch domain of Keap1 with a small molecule, Ligand1. In these two forms, the Ligand1 molecule occupied the binding site of Keap1 so as to mimic the ETGE motif of Nrf2, although the mode of binding differed in the two forms. Because the Ligand1 molecule mediated the crystal packing in both the forms, the influence of crystal packing on the ligand binding was examined using a molecular dynamics (MD) simulation in aqueous conditions. In the MD structures from the soaking form, the ligand remained bound to Keap1 for over 20 ns, whereas the ligand tended to dissociate in the cocrystallization form. The MD structures could be classified into a few clusters that were related to but distinct from the crystal structures, indicating that the binding modes observed in crystals might be atypical of those in solution. However, the dominant ligand recognition residues in the crystal structures were commonly used in the MD structures to anchor the ligand. Therefore, the present structural information together with the MD simulation will be a useful basis for pharmaceutical drug development. Abstract : Keap1 is useful target for the design of drugs that regulate the response to oxidative stresses. We determined two complex crystal structures of Keap1 with a small molecule ligand. The ligand binds to Keap1 so as to mimic the physiological substrate Nrf2. From molecular dynamics simulation results, the binding modes observed may be atypical in solution. Key residues for ligand binding are common between crystal and MD structures.